ANALYZING LANGUAGE ATTRITION - Dilnoza Nazarova; Abdusamadov Zafar Nurmatovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
“Language attrition” portrays the misfortune of, or changes to, linguistic and other highlights of a dialect as a result of declining utilize by speakers who have changed their etymological environment and dialect propensities. In such a circumstance there may, for case, be rearrangements within the tense framework or in certain properties of subordinate clauses; a few lexicon things might drop into neglect and phonetic highlights may be rebuilt. These changes can be influenced by highlights of the speaker’s environment, but too by his or her demeanors and forms of recognizable proof.